(untitled) (Revista cientifica In Vestigium Ire, 2020)
The detection of psychosocial risk factors in the organizations constitutes a valuable standard to fight stress and the diseases derived from it that interfere in the health and performance of the collaborators. In this sense, the present research had as objective to propose strategies to mitigate the extra‐ and intralaboral psychosocial risk factors in the domains of leadership, social relations and work demands. The developed study was of mixed type, the quantitative component was represented in the application of 85 surveys, and the qualitative in the application of 6 in‐depth surveys, as well as the selection to convenience of the literature. The results prove that there is a greater risk of stress, because there were difficulties in the evaluation of leadership styles, conflicts in coexistence and finally the appearance of labor stress affected the health of the workers. In the conclusions, it is recommended to apply strategies and mitigate the identified psychosocial risks.